GRK5 intronic (CA)n polymorphisms associated with type 2 diabetes in Chinese Hainan Island. - Zhenfang Xia; Tubao Yang; Zhuansuo Wang; Jianping Dong; Chunyan Liang (PLoS ONE)
A genome-wide association study had showed G-protein-coupled receptor kinase 5 (GRK5) rs10886471 was related to the risk of type 2 diabetes mellitus (T2DM) through upregulated GRK5 mRNA expression. Rs10886471 is located in the intron region of GRK5. However, the mechanism by which intronic SNP affects gene expression remains unclear, whether the effect on gene expression depends on the intronic short tandem repeat (STR) (CA)n splicing regulator or not. Here we investigated the STR (CA)n polymorphism in rs10886471 and further discussed its role in the T2DM risk of Chinese Hainan Island individuals. A total of 1164 subjects were recruited and classified into a normal fasting glucose (NFG) group, an impaired fasting glucose (IFG) group, an impaired glucose tolerance (IGT) group, and a T2DM group. STR (CA)n polymorphisms were detected through polymerase chain reaction and sequencing. Five intronic (CA)n alleles, (CA)15 to (CA)19, were identified in GRK5 rs10886471. Only the (CA)16 allele was significantly associated with increased prediabetes and T2DM risk [odds ratio (OR)>1, P<0.05]. Conversely, multiple alleles without any (CA)16 protected against prediabetes and T2DM (0<OR<1, P<0.05). In summary, rs10886471 acts as both an SNP and an STR. The rs10886471 intronic SNP causes GRK5 overexpression the subsequent risk of T2DM may be due to the rs10886471 intronic STR (CA)n splicing enhancer. Further studies should focus on verifying these finding using a large sample size and analyzing the splicing mechanism of intronic (CA)n in rs10886471.